2009
DOI: 10.15388/actpaed.2009.23.3050
|View full text |Cite
|
Sign up to set email alerts
|

Nuotolinis suaugusiųjų mokymas(is) mokymosi visą gyvenimą kontekste

Abstract: Socialinių mokslų (edukologijos) daktarė Vytauto Didžiojo universiteto Socialinių mokslų fakulteto Edukologijos katedra K. Donelaičio g. 58, LT-44044 Kaunas Tel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Understandably, qualitative participation in the study process is not easy, because a person's independence is determined by many different factors. A previous study conducted in Lithuania showed that the greatest motivation to participate in distance learning is personal interest and convenience [34].…”
Section: Discussionmentioning
confidence: 99%
“…Understandably, qualitative participation in the study process is not easy, because a person's independence is determined by many different factors. A previous study conducted in Lithuania showed that the greatest motivation to participate in distance learning is personal interest and convenience [34].…”
Section: Discussionmentioning
confidence: 99%
“…Pastaroji tendencija aiškintina tuo, kad nuotolinės studijos Lietuvoje nėra labai populiarios, nėra pakankamai išplėtota nuotolinių studijų bazė. Tai įrodo tyrimai, atlikti su aukštųjų mokyklų studentais (Zuzevičiūtė, Butrimaitė, Jarmakovienė, 2009;Rutkienė, Trepulė, 2009; ir kt.). Kaip pažymi Rutkienė, Trepulė (2009), nuotolinio mokymo elementai yra taikomi universitetuose, tačiau jie mažokai taikomi kitose švietimo institucijose.…”
Section: Aukštųjų Mokyklų Dėstytojų Akademinės Veiklos Gebėjimų Svarbunclassified
“…
According to the approved Lifelong Learning Strategy (2004) by the Ministry of Education and Science, Ministers of Social Security and Labour, the country must strive to involve NGOs and social partners in the development of adult education. According to Rutkienė, Trepulė (2009), the lifelong learning paradigm covers all areas of human learning, provides opportunities for people to learn throughout their lives. It is very important for those who have not used or had no access to education for various reasons, departed from the job market etc.
…”
mentioning
confidence: 99%